The Effects of Magnetic Exposure on the Nervous System: A study on the effects of low-strength low-frequency magnetic fields on neurotransmitter exocytosis and cell viability through ionic cyclotron resonance frequency. - Saveriades, George. (2017)
Abstract: This PhD dissertation focuses on the study of the effects of magnetic exposure on biological systems using amperometry techniques and viability assays. In our prior work based on the cyclotron resonance model, chromaffin cells in physiological saline and Ca2+-free media were exposed for 5 minutes to a 2.7 μT magnetic field, with frequency sweeps going from 30-60 Hz (targeting several ions involved in exocytosis) and 44-48 Hz (targeting specifically Ca2+ ions), with noticeable effects on exocytosis. The present study extended the work on chromaffin cells by covering frequency sweeps for different ions, manipulating the time of exposure and the strength of the magnetic field. Furthermore, amperometry was conducted on acute coronal brain slices, to demonstrate that the recorded effects could be measured on neuronal tissue. The viability of chromaffin cells and primary neuronal cultures exposed to magnetic fields was also addressed. The results demonstrate that cellular exocytosis is sensitive to the frequency of the magnetic field it is exposed to, the strength of the magnetic field and the duration of exposure. No significant effects were established with regards to the viability of the cells exposed to magnetic fields.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Electrical Engineering.; Advisors: Joseph Noonan, and Emmanuel Pothos.; Committee: George Sergiadis, and Brian Tracey.; Keywords: Electrical engineering, Neurosciences, and Electromagnetics.